A study to evaluate the clinical outcome of drug-eluting vs. bare-metal stents for acute coronary syndrome patients during commercial use in real setting - Patel, Chetan R.; Patel, Mandev B. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: This study compared clinical outcome of Drug Eluting Stents (DES) versus Bare Metal Stents (BMS) in coronary arteries in patients with Acute Coronary Syndromes. Methods: A retrospective, observational study was carried out in an inpatient setting of the private tertiary care hospital. Patients with >18 years, diagnosed for Acute Coronary Syndromes (ACS), required intervention in coronary artery with implantation of Drug Eluting Stents (DES) or Bare Metal Stents (BMS) were recruited in the study. The data had been collected from file or database of the hospital. All subjects were followed for major adverse cardiac event. Results: A total of 202 patients who underwent percutaneous coronary intervention (PCI) were enrolled into DES group (n=101) and BMS group (n=101). All patients were followed up at 1 month, 3 months, 6 months & 12 months for Major Adverse Cardiac Events (MACE). Clinical outcomes during 12 months were compared between DES group & BMS group. Overall MACE rates were reported non-significantly high in BMS group patients (14.85%) compare to DES group patients (8.91%) (p=0.458). However, DES group had lower rates of death (0.99% vs 1.98%, p=0.57), rate of MI (3.96% vs 4.95% p=0.73), rate of revascularization (1.98% vs 3.96% p=0.42) & rate of sub acute thrombosis (1.98% vs 3.96% p=0.42) and higher rate of bleeding (1.98% vs 0.99% p=0.57) compare to cohort-II. Conclusions: The use of DES in the setting of Acute Coronary Syndrome is associated with lower Major Adverse Cardiac Event (MACE) rate compared to BMS without compromising the overall safety over the course of one-year follow-up. The long-term safety of drug-eluting stents needs to be ascertained in large, randomized trials.